1969
DOI: 10.2337/diab.18.4.212
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Guinea Pig Antibodies to Beef Insulin, Chicken Insulin, and Cod Insulin to Neutralize Capybara Insulin

Abstract: Guinea pig and coypu insulins are the only mammalian insulins known to be non-neutralizable by antibody to beef insulin. A third non-neutralizable mammalian insulin, that of the capybara (carpincho, or hydrochoerus hydrochoerus) has been identified. Capybara pancreas yielded 0.5 U. extractable insulin per gram. An amount of guinea pig antibody to beef insulin sufficient to neutralize thirty times as much beef insulin did not significantly alter the increase in glycogen content produced by pancreatic capybara i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1981
1981

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Thus, it was found that guinea pig insulin was not neutralized by anti-bovine or anti-porcine insulin serum produced in the horse, sheep or rabbit (Goldsmith and Moloney 1957). Davidson et al (1968Davidson et al ( , 1969also showed that guinea pig, coypu and capybara insulins are not neutralized by anti-bovine insulin, but that insulins from the chinchilla (Chinchilla Laniger) and the muskrat (Ondatra), taxonomically more distant, are neutralized.…”
Section: ) Insulin the Fact That Antibody T O Beef Insulin Couldmentioning
confidence: 99%
“…Thus, it was found that guinea pig insulin was not neutralized by anti-bovine or anti-porcine insulin serum produced in the horse, sheep or rabbit (Goldsmith and Moloney 1957). Davidson et al (1968Davidson et al ( , 1969also showed that guinea pig, coypu and capybara insulins are not neutralized by anti-bovine insulin, but that insulins from the chinchilla (Chinchilla Laniger) and the muskrat (Ondatra), taxonomically more distant, are neutralized.…”
Section: ) Insulin the Fact That Antibody T O Beef Insulin Couldmentioning
confidence: 99%